2015
DOI: 10.1590/s1519-99402015000100013
|View full text |Cite
|
Sign up to set email alerts
|

Bagaço de cana-de-açúcar como volumoso exclusivo em dietas para ovinos

Abstract: <p>Objetivou-se avaliar o efeito de diferentes proporções de concentrado e bagaço de cana-de-açúcar como volumoso exclusivo em dietas para ovinos. Os consumos de matéria seca, matéria orgânica, proteína bruta, carboidratos não fibrosos e nutrientes digestíveis totais expressos em kg/dia, aumentaram linearmente com o aumento da proporção de concentrado na dieta. O mesmo comportamento foi observado para a digestibilidade da matéria seca. O que ocorreu de forma contrária para a digestibilidade da fibra em d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…This contrasts with the expected negative linear effect, since, according to Silva et al (2015), adding concentrate to the diet of feedlot sheep can negatively affect pH, and thus growth and performance of the fibrolytic bacteria responsible for ruminal degradation of dietary fiber, reducing NDF and ADF digestibility. Possibly the quadratic effects observed for NDFDC and ADFDC are associated with a reduced intake of these components (Table 2), and with an increase of protein concentration due to the inclusion of increasing levels of concentrate, as well as to the bicarbonate present.…”
Section: Variablesmentioning
confidence: 89%
“…This contrasts with the expected negative linear effect, since, according to Silva et al (2015), adding concentrate to the diet of feedlot sheep can negatively affect pH, and thus growth and performance of the fibrolytic bacteria responsible for ruminal degradation of dietary fiber, reducing NDF and ADF digestibility. Possibly the quadratic effects observed for NDFDC and ADFDC are associated with a reduced intake of these components (Table 2), and with an increase of protein concentration due to the inclusion of increasing levels of concentrate, as well as to the bicarbonate present.…”
Section: Variablesmentioning
confidence: 89%
“…Sales, Leite, Alves, Ramos e Nascimento (2013), no entanto, obtiveram nas mesmas condições na Paraíba, uma produtividade de 35t ha -1 .ano -1 colhidos com 710 dias após o plantio. Silva et al (2015b), analisando três clones de palma forrageira, verificou que a variedade Orelha de Elefante Mexicana (Opuntia stricta Haw. (Haw)) apresenta maior tolerância ao estresse hídrico, quando comparada às espécies do gênero Nopalea spp.…”
Section: Palma Forrageira: Cultivo E Uso Em Regiões Semiáridasunclassified
“…Besides raising the cost of the diet, concentrated feed, alters the ruminal fermentation pattern, with an increase in the propionate:acetate ratio (Han et al, 2014). Silva et al (2015) studying diets with sugarcane bagasse and concentrate observed that great proportions of concentrate increased propionate, the ratio propionate:acetate and decreased linearly the pH. These modifications in fermentation patterns also modify the ruminal biohydrogenation routes, with possible modification of the fatty acid (FA) profile of the milk (Jenkins et al, 2008).…”
Section: Introductionmentioning
confidence: 99%